Facility Improvement in a Thai Prison through Decentralized Management and Alternative Funding - Lawanyawatna, Sunaree (The prison journal, 2024)
Thai correctional institutions face budget constraints that hinder facility improvements. This study proposes a decentralized management approach using in-kind donations rather than central funding. The strategy includes partnering with manufacturers for rejected but usable materials and reusing excess construction materials from nearby projects. Benefits include tax breaks, lower disposal costs, improved prison facilities, inmates’ skill development, and environmental sustainability. A case study at the Thonburi Detention Center showed significant improvements at lower costs. Future research involves refining the approach with service design principles, a digital exchange platform, and introducing environmental credits to enhance participation and impact.